Impacto da saúde bucal na qualidade de vida de pacientes maiores de 50 anos de duas instituições públicas do município de Araraquara-SP - Alvarenga, Fábio Augusto de Santi [UNESP]; Henriques, Cristiane [UNESP]; Takatsui, Fabiana [UNESP]; Montandon, Andréia Affonso Barreto [UNESP]; Telarolli Júnior, Rodolpho [UNESP]; Monteiro, Ana Lucia Colabone de Castro; Pinelli, Camila [UNESP]; Loffredo, Leonor de Castro Monteiro; Pinelli, Camila [UNESP] (My University, 2011)
Introduction: Oral health can affect quality of life, and the OHIP-14 index (Oral Health Impact Profile) is useful for evaluating this impact. Objective: to investigate the impact of oral health conditions on the quality of life of patients over  50  years, assessing, initially, the consistency of the short form of the Oral Health Impact Profile index (OHIP-14). Material and method: A cross-sectional study was performed among 149 patients of two public institutions for routine dental (UNESP) and medical practice (Municipal). They were interviewed using the OHIP-14 formulary, assessing its internal consistency (Cronbach´s alpha coefficient) and the OHIP-mean (additive method). The patients were distributed according to sex, age, and education level. The comparisons of interest were made using Student´s t test at a 5% level of significance. Result: A total of consecutive patients (n = 149) participated of this study (87% response rate). Cronbach´s alpha coefficient was 0.78, denoting a good consistency of the OHIP index. The OHIP mean was 4.98. The most prevalently affected OHIP domains were dimensions of physical pain: painful aching (11.40%) and uncomfortable eating foods (21.50%). There was non-significant difference (p > 0.05) between the mean OHIP value in relation to each of gender, age, and education level. Conclusion: The OHIP-14 is a reliable instrument of assessing oral health-related quality of life, and among patients under routine practice, it was found a low impact of oral conditions on their quality of life in the studied institutions (UNESP and Municipal).

Introdução: A saúde bucal pode afetar a qualidade de vida das pessoas, sendo o índice OHIP-14 (Oral Health Impact Profile) de utilidade para avaliar este impacto. Objetivo: Estudar o impacto da saúde bucal na qualidade de vida de pacientes maiores de 50 anos, verificando-se, preliminarmente, a confiabilidade do índice OHIP-14. Material e método: Estudo transversal, em que se aplicou o formulário OHIP-14 a 149 pacientes em duas instituições públicas de atendimento de rotina em Clínica Odontológica (UNESP) e médico (Municipal). Estudou-se a consistência interna do índice aplicando-se o coeficiente alpha-Cronbach. O índice OHIP-14 foi obtido pelo método aditivo, sendo os pacientes distribuídos segundo gênero, faixa etária e nível de escolaridade. O teste t-Student foi usado para comparações de interesse, adotando-se um nível de significância de 5%. Resultado: A amostra compôs-se de 149 pacientes (87% de cobertura). A consistência interna para o índice OHIP-14 foi boa (alpha-Cronbach = 0,78). A média, para o índice OHIP-14, foi de 4,98. Houve predomínio da dor física, nos aspectos “sentir-se incomodado ao comer algum alimento” e “sentir fortes dores na boca”, com prevalências de 21,50 e de 11,40%, respectivamente. Houve diferença não-significativa entre o índice OHIP médio e cada uma das variáveis gênero, faixa etária e escolaridade (p > 0,05). Conclusão: O índice OHIP-14 apresentou consistência interna boa e mostrou ser baixo o impacto da saúde bucal na qualidade de vida de pacientes maiores de 50 anos em atendimento odontológico e médico de rotina nas instituições estudadas (UNESP e Municipal).
Oral health impact profile in the quality of life of patients over 50 years old of two public institutions of Araraquara city
Keywords: OHIP-14; Oral health; Quality of life; Self-perception; OHIP-14; Saúde bucal; Qualidade de vida; Autopercepção